Shock transmission through universal joint of cutter suction dredger. (1st August 2021) - Vijayan, K.; Barik, C.R; Sha, O.P.
Abstract: The dredger operation extended from protected water to harsher environments in recent years. This resulted in a change in design strategy. Understanding these complex dynamic interaction during the dredging operation using a Cutter Suction Dredger (CSD) can improve the production by reducing the downtime. CSD consists of the dredge hull, spud and the cutter shaft. A hybrid scaled model of the CSD is developed using Froude and Cauchy scaling for the different section of the CSD. The assembly was modelled in two sections. The spud hull assembly dynamics was modelled using WAMIT and ANSYS. The system was identified and reduced to a SDOF in the surge direction. The surge dynamics was coupled to the cutter shaft assembly using a roller support. Wave excitation acting on the assembly was determined using statistically linearised Morison equation. The assembly was linearised in frequency domain and transformed to state space and the temporal response was determined. A parametric study was carried out to understand the influence of the relative shaft dimensions and the coupling strength on the vibration transmission when subjected to an impulsive load. The results from the study indicated that shaft dimension asymmetry and coupling strength influences the vibration transmission. Highlights: Formulate a hybrid scaling strategy for the cutter suction dredger. Understand the interaction of the dredge hull, spud, soil and the cutter shaft. Develop the linearised dynamics of the cuter shaft subjected to wave loading. Understand the vibration transmission in the assembled dredge hull, spud and cutter shaft system. Analyse the effect of critical factors influencing the vibration transmission such as the coupling strength of universal joint and shaft dimensions.